EFFECT OF BANK INDONESIA SHARIA CERTIFICATES, DOMESTIC INTEREST RATES AND RUPIAH EXCHANGE RATES ON INDONESIA SHARIA STOCK INDEX (ISSI) - Fidian Nisa; Khoirunnisa Azzahra (Transpublika Publisher, 2022)
This study aims to determine the effect of Bank Indonesia Syariah Certificates (SBIS), Domestic Interest Rates and Rupiah Exchange Rates on the Indonesian Syariah Stock Index (ISSI) during the 2016 – 2020 period, which obtained as many as 60 data in this study. The sampling technique used in this study is non-probability sampling, namely by using saturated sampling, where all members of the population are used as samples. The method used in this research is descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing by using the EViews version 10 for Windows. The results showed that the data met classical assumptions such as normal distribution data, there was no multicollinearity, no heteroscedasticity and no autocorrelation. From the results of the partial hypothesis, Bank Indonesia Syariah Certificates (SBIS) and Domestic Interest Rates have an influence on the Indonesian Syariah Stock Index (ISSI). Meanwhile, the Rupiah Exchange Rate has a negative effect on the Indonesian Sharia Stock Index (ISSI). Based on the results of the hypothesis simultaneously shows that Bank Indonesia Syariah Certificates (SBIS), Domestic Interest Rates and Rupiah Exchange Rates have an influence on the Indonesian Syariah Stock Index (ISSI).